Code-Mixing In English Learning of SD Teladan Yogyakarta - Tri Jampi Setiyorini; Septiana Wahyu Setyaningrum (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2021)
Based on the KTSP Curriculum, English is a compulsory subject which must be learned by students of elementary schools, one of them is in SD Teladan Yogyakarta. To improve students’ understanding about English materials, the English teacher uses code-mixing in English learning. This research aimed at analyzing types of processes of code-mixing and describing the reasons of code-mixing in English learning of SD Teladan Yogyakarta. The type of this research was descriptive case study. The subjects of the study were an English teacher, 25 students of class 1A, 25 students of class 1B, and 25 students of class 1C. To examine types of processes of code-mixing, the researchers recorded the English learning in the classroom. The researchers also collected the data by using an interview to an English teacher to investigate the reasons of using code-mixing. After that, all data are transcribed and analyzed based on Muysken’s theory (2000) and Hoffmann’s theory (1991). The result of the analysis shows that types of processes of code-mixing in English learning of SD Teladan Yogyakarta are insertion (70.09%), alternation (3.42%), and congruent lexicalization (26.49%). From the result of the interview, the reasons for code-mixing are for talking about a particular topic, for quoting somebody else, for being empathic about something, for interjections, for repetition used for clarification, for clarifying speech content for interlocutors, and for expressing group identity.